RANCANG BANGUN SISTEM INFORMASI PENCATATAN PEMBAYARAN IURAN BERBASIS WEB Pada UPTD Pemakaman Kota Bogor. - Mia Setya Bandiyani (2020)
The recording of UPTD funeral fee payments in the city of Bogor is one of the important things in conducting funeral land lease transactions from experts to the UPTD with the aim to improve the payment data coming in every period. Recording payments is managed by employees manually and using applications, namely Microsoft Excel and Microsoft Word in data storage and processing, besides that the system is still stand-alone desktop-based so that the dissemination of information is not conveyed directly and the system does not have data backup. Making information systems for recording payment of Funeral UPTD fees selected by web-based researchers. Then the research methods used, namely the data collection method using interviews and observation, the method of accessing the PIECES system to analyze the strengths and weaknesses of the running system, the UML system modeling method to complete the supported system concepts, and the Waterfall system design method was chosen to suit system design is carried out in accordance with the stages so as to minimize errors in the installation workmanship. Then in making the system the researchers chose the PHP and MySQL Programming Languages as supporting database management systems. The results of this study are expected to be useful for users in recording activities of the Bogor City Cemetery UPTD fees. Keywords: Information Systems, Website, PHP, Waterfall, fees